Platinum nanoparticles produced by EG/PVP method: The effect of cleaning on the electrooxidation of glycerol - Fernández, Pablo Sebastián (2013)
Carbon supported Pt nanoparticles (NPs) have been prepared through polyols method using PVP. As observed with a large number of surfactants employed in NPs synthesis, it is very difficult to attain an efficient NPs cleaning, which is a fundamental requirement in catalysis researches. The aim of this paper was to obtain clean NPs, beginning by using “soft” methods, in order to keep unaltered both the NPs size and shape; however, an important surfactant remnant was observed. Consequently, it was performed an electrochemical cleaning through PVP and glycolate electro-oxidation, being accompanied with important perturbations of NPs atoms and dissolution and re-deposition of Pt. Finally, the performance of the catalyst towards the glycerol electro-oxidation reaction (GER), before and after the cleaning process was studied. In addition, we demonstrate how the impurities bring about poor reproducibility in this kind of experiments due to the fact that the cleaning process is occurring at the same time that the GER and because cleaning extent along cycles varies for each independent experiment.